Evaluation of propagation technique of Dragon fruit (Hylocereus polyrhizus) on various media - Baby Laltlanhlui; Alila, Pauline; S Jamir; A Sarkar; P Neog (Current Horticulture, 2025)
A study was carried out on dragon fruit (Hylocereus polyrhizus L.) with two factor randomized block design replicated five times at School of Agricultural Sciences, Nagaland University, Medziphema, Nagaland, during 2022-23. The treatments consisted of four types of media (sand, sand + FYM, sand + vermicompost and sand + leaf compost) and two cladode parts (upper half and lower half ). The shoot parameters such as number of primary and secondary shoots (5.66 and 1.99), number of aereoles (30.77) and fresh weight and dry weight of shoots (103.66 g and 0.94 g) were recorded best under sand + compost, which were statistically at par with sand + vermicompost. The lower cladode part resulted in better shoot parameters, viz. number of primary and secondary shoots (4.84 and 1.68), length of primary and secondary shoots (36.30 cm and 27.14 cm), number of aereoles (27.72), fresh weight and dry weight of shoots (99.86 g and 0.80 g) over the upper cladode part. Similarly, highest number of primary and secondary roots (7.90, 29.08), longest root length (23.36 cm) and fresh and dry weight of roots (2.04 g, 0.80 g) resulted in lower cladode cuttings. The number of primary and secondary roots (8.29, 35.73), fresh and dry weight of roots (2.27 g, 0.94 g) were significantly more under sand + compost. Sand medium triggered the longest root length (28.79 cm). The use of sand + compost or sand + vermicompost with lower half cladode part can effectively enhance the growth of dragon fruit cuttings.